2005
DOI: 10.1002/pmic.200401313
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes in the pressure overloaded right ventricle after 6 weeks in young rats: Correlations with the degree of hypertrophy

Abstract: Right ventricular (RV) hypertrophy is an important problem in congenital heart disease. We determined the alterations in phenotype that occur in the initial phase of RV hypertrophy and their possible correlations with the degree of hypertrophy. Therefore, we performed a differential proteomic profiling study on RV hypertrophy using an animal model of pulmonary artery banding (PAB) in parallel with hemodynamic characterization. The RV homogenates were subfractionated in myofilament and cytoplasmic proteins, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 48 publications
5
55
2
Order By: Relevance
“…Heat shock proteins are ubiquitously expressed, and to protect cardiomyocytes from injury, heat shock proteins within the cell increase in response to externally applied stressors. In contrast with our (8).…”
Section: H704contrasting
confidence: 54%
“…Heat shock proteins are ubiquitously expressed, and to protect cardiomyocytes from injury, heat shock proteins within the cell increase in response to externally applied stressors. In contrast with our (8).…”
Section: H704contrasting
confidence: 54%
“…One of the challenges is to identify the turning point from compensated RV hypertrophy to (irreversible) RV failure. In a previous study, we reported the changes in the myocardial protein expression in response to RV pressure overload (12). We demonstrated alterations in expression of metabolic proteins, compatible with a shift from fatty acid to carbohydrate metabolism.…”
Section: Relevance Of the Studymentioning
confidence: 96%
“…A major advantage of the use of these small disease models is that cardiac material can be easily sampled to study critically involved molecular changes over time and the possibility to study effects of transgenesis and gene ablation (2,5,22,23,34). Recently, we performed a proteomic profiling study on RV hypertrophy showing multiple expression and posttranslational changes in metabolic, stress, and myofilament proteins (12). To interpret these molecular findings in terms of possible mechanisms involved in RV remodeling, an accurate assessment of RV function is required, preferably by using load-independent parameters of cardiac contractility (13,24,29,30).…”
mentioning
confidence: 99%
“…Gels were scanned and aligned in Syquest (Biorad) to quantify differential expression of proteins. 11 Selected protein spots were excised, trypsin digested, and subjected to matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry for protein identification. Peptide mass fingerprints were analyzed using the Mascott protein database (www.matrixscience.com) and the Mowse score automatic cutoff.…”
Section: Renin-ang System Genes and Ang Ii-regulated Genesmentioning
confidence: 99%